2010
DOI: 10.1115/1.4002025
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Investigation of Ankle Injury Under Excessive External Foot Rotation in the Human Cadaver

Abstract: Numerous studies on the mechanisms of ankle injury deal with injuries to the syndesmosis and anterior ligamentous structures but a previous sectioning study also describes the important role of the posterior talofibular ligament (PTaFL) in the ankle's resistance to external rotation of the foot. It was hypothesized that failure level external rotation of the foot would lead to injury of the PTaFL. Ten ankles were tested by externally rotating the foot until gross injury. Two different frequencies of rotation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 21 publications
3
71
1
Order By: Relevance
“…Foot constraint may influence subtalar motion and the movement of bones in the foot, thereby influencing the mode of injury during external foot rotation. Recent studies 41,44 in our laboratories, using potted and taped foot constraints, also document altered failure characteristics of the ankle under external foot rotation. In a study with a potted foot, the PTaFL was injured in 5 of 10 ankles; fibular fractures were generated in 4 ankles; a single incident of an anterior deltoid ligament rupture was noted.…”
Section: Introductionmentioning
confidence: 82%
“…Foot constraint may influence subtalar motion and the movement of bones in the foot, thereby influencing the mode of injury during external foot rotation. Recent studies 41,44 in our laboratories, using potted and taped foot constraints, also document altered failure characteristics of the ankle under external foot rotation. In a study with a potted foot, the PTaFL was injured in 5 of 10 ankles; fibular fractures were generated in 4 ankles; a single incident of an anterior deltoid ligament rupture was noted.…”
Section: Introductionmentioning
confidence: 82%
“…A second validation of the ankle model was performed while simulating a cadaver study [22] that investigated ankle injury due to excessive external foot rotation. To simulate this cadaver experiment in the computational model, an input external foot rotation of 40° was used, based on the average failure rotation documented in the cadaver study.…”
Section: Model Validationmentioning
confidence: 99%
“…Reported ligament stiffness values have a relatively large range [23] . To assess the sensitivity of simulations and in order to further validate the computational model, the effect of variations in ligament stiffness on model outcomes was studied by performing an additional simulation that mimicked a previous experimental setup [22] . To quantify the effect of ligament stiffness, first, all of the ligament spring stiffness were together either increased by 25% or decreased by 25%.…”
Section: Model Sensitivity Analysismentioning
confidence: 99%
“…Haraguchi and Armiger [10] showed that external rotation of the foot while in pronation first produced damage to the AITFL, followed by medial injury to the deltoid ligament. Wei et al [11]showed that ankle external rotation with an everted foot is also more likely to disrupt the AITFL, first producing lateral translation and external rotation of the talus. Conversely, external rotation of a neutral foot is more likely to initially result in deltoid ligament injury [11], with subsequent injury to the AITFL and syndesmotic ligaments [12].…”
Section: Injury Mechanicsmentioning
confidence: 99%
“…Wei et al [11]showed that ankle external rotation with an everted foot is also more likely to disrupt the AITFL, first producing lateral translation and external rotation of the talus. Conversely, external rotation of a neutral foot is more likely to initially result in deltoid ligament injury [11], with subsequent injury to the AITFL and syndesmotic ligaments [12]. Disruption of at least two lateral ligaments and injury to the deltoid ligament are necessary for complete syndesmosis instability.…”
Section: Injury Mechanicsmentioning
confidence: 99%